The GNU Make Book. Issue 5 (May 2015) - Unknown
Abstract : A significant proportion of those people who encounter the GNU Make utility do little more than invoke the program in its barest form. But there is a lot more to this software that those people imagine. And if you are a security practitioner or researcher who has cause to write software, familiarity with the full power of Make can be a considerable asset.